Paper device combining CRISPR/Cas12a and reverse-transcription loop-mediated isothermal amplification for SARS-CoV-2 detection in wastewater - Cao, Haorui; Mao, Kang; Ran, Fang; Xu, Pengqi; Zhao, Yirong; Zhang, Xiangyan; Zhou, Hourong; Yang, Zhugen; Zhang, Hua; Jiang, Guibin (American Chemical Society, 2022)
Wastewater-based surveillance of the COVID-19 pandemic holds great promise; however, a point-of-use detection method for SARS-CoV-2 in wastewater is lacking. Here, a portable paper device based on CRISPR/Cas12a and reverse-transcription loop-mediated isothermal amplification (RT-LAMP) with excellent sensitivity and specificity was developed for SARS-CoV-2 detection in wastewater. Three primer sets of RT-LAMP and guide RNAs (gRNAs) that could lead Cas12a to recognize target genes via base pairing were used to perform the high-fidelity RT-LAMP to detect the N, E, and S genes of SARS-CoV-2. Due to the trans-cleavage activity of CRISPR/Cas12a after high-fidelity amplicon recognition, carboxyfluorescein-ssDNA-Black Hole Quencher-1 and carboxyfluorescein-ssDNA-biotin probes were adopted to realize different visualization pathways via a fluorescence or lateral flow analysis, respectively. The reactions were integrated into a paper device for simultaneously detecting the N, E, and S genes with limits of detection (LODs) of 25, 310, and 10 copies/mL, respectively. The device achieved a semiquantitative analysis from 0 to 310 copies/mL due to the different LODs of the three genes. Blind experiments demonstrated that the device was suitable for wastewater analysis with 97.7% sensitivity and 82% semiquantitative accuracy. This is the first semiquantitative endpoint detection of SARS-CoV-2 in wastewater via different LODs, demonstrating a promising point-of-use method for wastewater-based surveillance.
Keywords: SARS-CoV-2; CRISPR/Cas12a; RT-LAMP; paper device; wastewater